Optimasi Metode 1H-NMR Profiling pada Rimpang Kunyit (Curcuma domestica) - Dwiseptianti, Caroline; Susanto, Febri Adi; Purwestri, Yekti Asih; Nuringtyas, Tri Rini (Universitas Muhammadiyah Surakarta, 2019)
The use of medicinal plants is increasing due to the lack of side effects caused and the number of bioactive compounds that cannot be represented by synthetic chemical synthesis compounds. However, the management and use of natural medicines for the main handling of diseases are often hampered by the quality of the ingredients which are low and unstable. The standardized quality control system of OAI (Indonesian Natural Medicine) is the main key to improve clinical assurance and safety of the use of herbal medicines in Indonesia. One of the medicinal plants known to the public is Curcuma longa L. (turmeric). The main active components contained in turmeric are curcumin, demetoksikurkumin, bis-demetoksikurkumin, and ar-turmeron. Information about the quality of turmeric is needed in its use as a raw material for drugs so we need an analytical technique that is able to identify the diversity of metabolite profiles of active compounds. In this research, an optimization method is used to improve efficiency in the extraction of turmeric rhizome metabolites so that the best solvent concentration is known for the analysis of fingerprinting secondary metabolites with 1H-NMR 500 MHz spectroscopy in turmeric rhizomes. The results were analyzed with MNOVA software and chemical shift obtained compared with the reference. From the results obtained a concentration of methanol-d4 (CD3OD) 100% able to extract curcumin better than other solvents. The solvent is able to extract saccharide (sugar) compounds in the form of sucrose, amino acids and fatty acids in the form of methionine, glutamine, acetate, and glycero phospho choline.